Terpaan Informasi Pinjaman Online di Media Online dan Terpaan E-WOM di Grup Facebook Pinjaman Online dengan Tingkat Pengetahuan Masyarakat dalam Penggunaan Pinjaman Online - Arfian Muhammad Hakim; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Fintech lending in Indonesia is one of the innovations in financial products and services that has been present in the past 5 years in Indonesia to provide assistance in accessing consumer consumptive funds via smartphones. However, the use of fintech lending that are not balanced with sufficient knowledge in the use of fintech lending causes new problems to form due to user misunderstandings which lead to a high risk of using them to cause casualties. Several ways to increase public knowledge are through online loan information in online media and discussions in the online loan facebook group. This also relates to the habits of Indonesian people who seek information on financial products and services using the Internet. This study aims to see whether there is a relationship between exposure to online loan information and E-WOM in the online loan Facebook group and the level of public knowledge in the use of fintech lending. This research is a quantitative type. The sample in this study were 100 people with the criteria of men or women aged 19-34 years, had seen / read online loan information in online media in the last month, and had read / been active in discussions on online loan facebook groups in the last month. Based on the research results, the variables of information exposure and e-wom exposure have a significant relationship to the level of public knowledge in the use of fintech lending. This is obtained from the results of the significance test of the two hypotheses carried out . In addition, the two independent variables also have a positive relationship with the variable the higher the community is exposed to information / exposure to e-wom, the higher the level of knowledge. However, although the relationship between the two independent variables and the variable can be said to be positive and significant, the two independent variables have a weak closeness to the variable assessed from the values shown.